Students’ Career Decision-Making Difficulties: A Comparative Study Based on Ethnic Background in Indonesia - Fajriani Fajriani; Mamat Supriatna; Abu Bakar; Fitra Marsela (STAI Hubbulwathan Duri, 2024)
Career decision-making is influenced by cultural context, impacting students’ choices and the challenges they face. This study investigates factors contributing to career decision-making difficulties among students from different ethnic backgrounds in Indonesia. A survey was conducted among 601 students from three Indonesian universities, spanning cohorts from 2020 to 2023. Data was collected using a validated career decision-making scale based on the taxonomy of career decision-making difficulties. Analysis was primarily descriptive, focusing on factors that hinder effective career choices. The findings indicate that indecisiveness and dysfunctional beliefs are key factors affecting career decision-making difficulties across ethnic groups. Indecisiveness, characterized by delaying decisions due to anxiety and uncertainty, and dysfunctional beliefs, encompassing unrealistic assumptions about career paths, emerged as significant barriers. While differences in ethnic backgrounds contributed to varying levels of difficulty, high motivation was consistently observed across all groups, indicating an absence of motivational issues. The results underscore the need for culturally responsive counseling in universities. Understanding that ethnic background influences career decision-making challenges can guide counselors in providing tailored support. Ethnically sensitive approaches may address the specific difficulties faced by diverse groups, improving career counseling outcomes. This study highlights the role of cultural factors, particularly ethnic differences, in shaping career decision-making difficulties among Indonesian students. Future research should expand to include a broader range of ethnic groups to deepen understanding of Indonesia’s cultural diversity in career decision contexts.